2020
DOI: 10.1002/kjm2.12271
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of autophagy, glucose uptake, and glycolysis under dengue virus infection

Abstract: We previously reported that dengue virus (DENV)‐induced autophagy plays a promoting role in viral replication and pathogenesis both in vitro and in vivo. Although it is known that DENV infection increases glycolysis, which promotes viral replication, the role of glucose metabolism together with autophagic activity in DENV replication remains unclear. In this study, we reveal that DENV2 infection increased autophagic activity, glucose uptake, protein levels of glucose transporter‐1 (GLUT1), and glycolysis rate‐… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 37 publications
1
21
0
Order By: Relevance
“…We reveal that DENV2 infection increased autophagic activity, glucose uptake, protein levels of glucose transporter‐1, glycolysis rate‐limiting enzyme hexokinase‐2 (HK2), and viral replication both in vitro and in vivo. We further confirmed that DENV‐induced autophagy induces lactate pathway‐independent glycolysis and viral replication 63 . Others reported that DENV infection triggers the release of autophagy‐related vesicles and the infection of other cells as well as the evasion of immune system surveillance 64 .…”
Section: Diseases Related To Aberrant Metabolism and Autophagysupporting
confidence: 80%
“…We reveal that DENV2 infection increased autophagic activity, glucose uptake, protein levels of glucose transporter‐1, glycolysis rate‐limiting enzyme hexokinase‐2 (HK2), and viral replication both in vitro and in vivo. We further confirmed that DENV‐induced autophagy induces lactate pathway‐independent glycolysis and viral replication 63 . Others reported that DENV infection triggers the release of autophagy‐related vesicles and the infection of other cells as well as the evasion of immune system surveillance 64 .…”
Section: Diseases Related To Aberrant Metabolism and Autophagysupporting
confidence: 80%
“…We previously reported that DENV2 and EV71 infection-induced autophagy promotes viral replication and pathogenesis [17][18][19][20][21][22]. DENV2 infection activates the autophagy machinery to form autophagosomes.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, DENV infection induced-autophagy also regulates cellular mechanisms, such as lipid metabolism and DENV2 induced-autophagy selectively engulfs the lipid droplets followed by the release of free fatty acids, which are converted to β-oxidation to produce ATP and promote DENV replication [24]. Furthermore, we previously reported that DENV2-induced glycolysis and ER stress increases autophagy activity, viral replication and pathogenesis through different signaling pathways both in vitro and in vivo [17,18]. Moreover, DENV NS4A protein can also induce autophagy through the activation of unfolded protein response (UPR) [25].…”
Section: Introductionmentioning
confidence: 99%
“…In this study, we identified the intranasal transmission of DENV under experimental conditions for the first time to facilitate a better understanding of non-vector-borne disease outbreaks in DENV endemic areas. To determine whether DENV can infect experimental mice through the intranasal route, BALB/c suckling mice, which are widely used in DENV research [ 22 , 23 ], and adult IFN-α/β receptor-deficient mice (A6 mice), which are susceptible to DENV [ 24 ], were exposed to dengue virus serotype 2 (DENV-2) through intranasal inoculation.…”
Section: Introductionmentioning
confidence: 99%